Rasayana herbs for longevity: An ayurvedic and contemporary appraisal - Vishal Kumar; Tanuja Manoj Nesari; Shivani Ghildiyal; Rahul Sherkhane (Wolters Kluwer Medknow Publications, 2021)
Objective: To explore Rasayana herbs ascribed in Ayurveda classics and their contemporary appraisal for Rasayana potential. Data Source: Classical Ayurvedic review of Rasayana herbs were done from three distinguished Ayurveda classics (Charaka Samhita, Sushruta Samhita and Ashtang Hridaya) known as Brithattrayi. The contemporary review of those classical herbs was done from PubMed and other reputed databases. Review Methods: The classical Ayurveda review was done manually from Charaka Samhita, Sushruta Samhita and Ashtanga Hridaya. The single herbs mentioned in specifically dedicated Rasayana chapters of these classics (Charaka Chikitsa 1, Sushruta Chikitsa 27, 28, Ashtanga Hridaya Uttarsthana 39) were gathered. The botanical identity of the herbs were taken from "The plant list.org". The contemporary review of those classical herbs mentioned as Rasayana in Ayurveda classics were done from PubMed and other databases. The searching key was Latin name of drug/herb+Rasayana activity. Results: Total 39 herbs were enumerated in Brihattrayi, among them 21 are in Charaka Samhita, 12 in Sushruta Samhita and 21 are from Ashtanga Hridaya, few of them are Bhallataka, Mandukaparni, Guduchi, Varahikanda, Soma, Tuvaraka, Vacha and Bhringaraja. Most of the herbs mentioned as Rasayana are evaluated scientifically for their antioxidant, immunomodulatory and nootropic potential. These reported activities of herbs support their Rasayana property. Conclusion: These studies indicate that daily damage of cells leads to early ageing and occurrence of many diseases. Rasayana herbs through their anti-oxidant, immunomodulatory and nootropic potential protect the damage which contribute towards health and longevity.